Impacts of Wheat Enzymatic Defense Mechanisms Response to Cereal Cyst Nematode (Heterodera avenae) Infection - Manisha; Baheti, B. L.; Abhi, Ramavath; Kumar, Deepak; Kumhar, R. N.; Jain, Devendra (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Biochemical trial was conducted to find out the variation in enzymic activities (PO, PPO, and PAL) infested with Heteroderaavenaeon wheat under cage house conditions. Results exhibited highest enzymatic activities (PO, PPO, and PAL) with application of chemical treatment (fluopyram 34.48% SC at 5 ml/kg seed). The chemical treatment significantly reduced nematode reproduction, as indicated by number of females per 5g root (9.10), cysts per 200 cc soil (12.45) and final larvae population per 200 cc soil (212.70).